Projeto Manuelzão: uma estratégia socioambiental de transformação da mentalidade social - Apolo Heringer Lisboa (2012)
This thesis has the purpose of studyng the historical reconstruction ofManuelzão Project (PMz-UFMG), through an analysis of its conceptual framework, and the results from its strategy of action that has consisted of the whole mobilization of society in order to bring back fish to Rio das Velhas, a river basin in state of Minas Gerais. The data analyzed in this study are part of the Manuelzão Project, linked to the Rural Internship of the Department of Social and Preventive Medicine, Faculty of Medicine, Federal University of Minas Gerais. From this collection, were analyzed,in addition to data collected in surveys of biomonitoring, reports of university extension activities, diaries produced by the trainees from different fields of knowledge and the documents that provide guidance to the day-todayPMz, as well as projects social mobilization that have been developed in the evaluated years in the period from 1997 to 2010. This thesis is divided into 6 parts. Introduction, in which it describes the reasons that led us to present a thesis on this subject. First chapter, in which it rescues the Manuelzão Project in the context of environmental struggles.Second chapter, tells the story of Rio das Velhas, incorporating Manuelzãos memory a honored character. The third chapter explains the strategies that were used in teaching, research and extension in order to build a project based on transdisciplinarity. Fourth chapter, analyzes the results of action to mobilize the Manuelzão Project on the Basin of the river named Rio das Velhas. And finally, we present General Considerations from the gaze of the researcher